2011
DOI: 10.1007/s10750-011-0909-8
|View full text |Cite
|
Sign up to set email alerts
|

Importance of seagrass vegetation for habitat partitioning between closely related species, mobile macrofauna Neomysis (Misidacea)

Abstract: Seagrass meadows provide both habitats and a range of food sources for macrofaunal communities. These functions facilitate the coexistence of less mobile invertebrates (in comparison with mysids, such as amphipods) that are associated with seagrass leaves, and may also enhance the coexistence of highly mobile invertebrates such as mysid. We investigated the function of seagrass in supporting the coexistence of two mysid species, Neomysis awatschensis and N. mirabilis. These taxa are dominant in seagrass ecosys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…From the perspective of macroinvertebrate functional diversity, the different patterns of metacommunity structure among functional groups shown in this study could be explained by the variation in ecosystem functions performed by the faunal community in different seagrass patches. For example, the small contribution of environmental controls in determining community structure in the DF and BF groups, but their strong association with seagrass patches (as reported by Barberá-Cebrián et al, 2002;Yamada et al, 2007b;Yamada and Kumagai, 2012), implies that the existence of patchy seagrass alone -without consideration of the vegetation traits -determines the community structure of the DF and BF groups. If so, the existence of more or less patchy seagrass should elicit the assembly of the DF and BF groups and thus ensure the ecological functions provided by these functional groups.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…From the perspective of macroinvertebrate functional diversity, the different patterns of metacommunity structure among functional groups shown in this study could be explained by the variation in ecosystem functions performed by the faunal community in different seagrass patches. For example, the small contribution of environmental controls in determining community structure in the DF and BF groups, but their strong association with seagrass patches (as reported by Barberá-Cebrián et al, 2002;Yamada et al, 2007b;Yamada and Kumagai, 2012), implies that the existence of patchy seagrass alone -without consideration of the vegetation traits -determines the community structure of the DF and BF groups. If so, the existence of more or less patchy seagrass should elicit the assembly of the DF and BF groups and thus ensure the ecological functions provided by these functional groups.…”
Section: Discussionmentioning
confidence: 89%
“…Boström et al, 2006;Yamada et al, 2007a). For example, it suggested that habitat selections are similar among mysid species in seagrass meadow (Yamada and Kumagai, 2012). Namely, many mysid species occur (i.e., increase their biomass) at same sites with same periods (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation